Kinetic modeling impacts of relative humidity, storage temperature, and air flow velocity on various indices of hen egg freshness. (6th August 2018) - Yimenu, Samuel Mezemir; Koo, Junemo; Kim, Ji-Young; Kim, Jong-Hoon; Kim, Byeong-Sam
ABSTRACT: Storage experiments were conducted to study the impacts of the environmental factors (temperature (T) (°C), relative humidity (RH) (%), and air flow velocity (VEL) (m/s)) on the hen egg quality indices and to develop kinetic model(s) for freshness prediction. VEL had negligible effect on relative weight loss (RWL). All factors had significant effect on Haugh unit (HU) but only T impacted S -ovalbumin content (SO). Fitted regression lines for the RWL and the HU had determination coefficient (R 2 ) of 0.996 and 0.95, respectively. The HU equation reflected impacts of all factors, and the impact of temperature shift-up increases the HU decrease, where the impact decreases with RH and increases with flow velocity. Kinetic model for SO was developed using isothermal (5, 10, 20, 25, and 28.5°C) conditions and validated under dynamic (10 to 20 and 10 to 28.5°C) conditions. The accuracy and bias factor values were 1.091 and 0.917 at 10 to 20°C and 1.206 and 1.204 at 10 to 28.5°C, respectively, which indicates that the SO model performed well. The SO model can be used along with the HU model (as the HU model can reflect the combined effect of temperature, humidity, and air flow velocity) to predict hen egg freshness at 5 to 28.5°C storage condition.